PEDOMAN PEMIDANAAN DALAM REKONSTRUKSI SISTEM HUKUM PIDANA NASIONAL 2023-2024 - Supriadin, Supriadin (Lex Jurnalica, 2024)
AbstractSentencing guidelines start from the main idea that the criminal law system is a unified system with a purpose (purposive system) and punishment is only a tool, a means to achieve goals which are an integral part of the sub-system of the entire criminal system. Regarding the status, position and guidelines for punishment in the substantive criminal system or national criminal law system. That the three main problems of criminal law are criminal acts (strabaarfeit, criminal act, actus reus), mistakes (schuld, guilt, mens rea). Method is the main method used to achieve a goal, to achieve the level of accuracy, quantity and type encountered. The guidelines for imposing criminal penalties in Article 55 paragraph (1) contain matters that the judge must consider before imposing a crime or sanction, namely the fault of the perpetrator of the criminal act, the motive and purpose of committing the criminal act, the inner attitude of the perpetrator of the criminal act, whether the criminal act was committed with planning, method of committing the crime, attitudes and actions of the perpetrator after committing the crime, life history and socio-economic conditions of the perpetrator of the crime. Reconstruction is rebuilding the national criminal law system. This term is very closely related to the issue of law reform and law development, especially related to reform, development of the criminal law system (penal system reform/development) or often referred to briefly as penal reform. The legal system (legal system) which consists of legal substance, legal structure and legal culture, means reform of the criminal law system (penal system reform). Keywords : Sentencing Guidelines, System Reconstruction, National Criminal Law AbstrakPedoman pemidanaan bermula dari pokok pikiran bahwa sistem hukum pidana merupakan satu kesatuan sistem yang bertujuan (purposive system) dan pidana hanya merupakan alat, sarana untuk mencapai tujuan yang merupakan bagian integral sub-sistem dari keseluruhan sistem pemidanaan. Mengenai kedudukan, posisi, dan pedoman pemidanaan dalam sistem pemidanaan substantif atau sistem hukum pidana nasional. Bahwa ketiga masalah pokok hukum pidana yang berupa tindak pidana (strabaarfeit, criminal act, actus reus), kesalahan (schuld, guilt, mens rea). Metode merupakan cara yang utama yang digunakan untuk mencapai suatu tujuan, untuk mencapai tingkat ketelitian, jumlah dan jenis yang dihadapi. Pedoman penjatuhan pidana di dalam Pasal 55 ayat (1) memuat mengenai hal-hal yang harus dipertimbangkan hakim sebelum menjatuhkan pidana atau sanksi adalah tentang kesalahan pembuat tindak pidana, motif dan tujuan melakukan tindak pidana, sikap batin pembuat tindak pidana, apakah tindak pidana dilakukan dengan berencana, cara melakukan tindak pidana, sikap dan tindakan pembuat sesudah melakukan tindak pidana, riwayat hidup dan keadaan social ekonomi pembuat tindak pidana. Rekonstruksi adalah menmbangun kembali sistem hukum pidana Nasional. Istilah itu sangan berkaitan erat dengan masalah law reform dan law development, khususnya berkaitan dengan pembaharuan, pembangunan sistem hukum pidana (penal system reform/ development) atau sering disebut secara singkat dengan istilah penal reform. Sistem hukum (legal system) yang terdiri dari legal substance, legal structure dan legal culture, maka pembaharuan sistem hukum pidana (penal system reform). Kata kunci: Pedoman Pemidanaan, Rekonstruksi Sistem, Hukum Pidana Nasional.